ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PADA TENAGA KERJA BANTUAN (HONORER) DINAS PERHUBUNGAN KOTA BALIKPAPAN: Rahajeng Cahyaning Putri Cipto - ajeng cipto (Jurnal GeoEkonomi, 2021)
In carrying out the functioning of the government of the Balikpapan subdistrict government, the role of outsourced workers is needed to maintain the operational activities in the field. The number of outsourced employees reached 46 people who became total respondents in the implementation of their duties were divided into 10 groups of fields. With the number of operational workers that much, the performance of the transportation service is still considered low. Therefore this study aims to determine the effect of work discipline, compensation, work motivation and competention on the performance of outsourcing employees. Type of research used in this research is quantitative research method. Data collection techniques were conducted through interviews, questionnaires and observations. Testing The reliability of the questionnaire in this study was assisted by SPSS 21 software. The analysis technique used in this study was F-test, t-test and simultaneous discussion. The results of the F-test show that the variables of Work Discipline, Compensation, Work Motivation and Competention of Cooperation together (simultaneously) have an effect on outsourced employee performance, whereas from the T-test results, motivation and Competention variables affect the performance when the work discipline and compensation variables have no effect significantly to performance. Based on the results of simultaneous test or F test F calculate can be concluded that the variable of Work Discipline, Compensation, Work Motivation And Competention simultaneously have a significant influence on employees Performance.